Evaluation of the Implementation of Furniture Independence Development for Prisoners at Class IIB Manokwari Prison - Pedro Richardo William Senandi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Guidance for prisoners is very important because the correctional system itself emphasizes reintegration where prisoners must have such good skills that when they return to society they can be well accepted by society. by having good enough skills this can be realized, one of which is by following the existing guidance program, one of which is the guidance program. To discuss the problems in this study, the information or data obtained can be adjusted to the existing theory, namely regarding the Evaluation of the Implementation of the guidance program in Prison. In the form of an effort to implement an independence guidance program, of course, an evaluation is needed to find out what obstacles make the guidance not run well. This study uses a research design in the form of a descriptive case study where all conclusions will be described in the form of a description that is linked to the theory and findings. The discussion in this study will basically discuss the results of the researcher's findings during the field to collect primary data in compiling a scientific paper in the form of a thesis. In order to conduct a discussion, the researcher briefly reviewed a problem in this study, namely the Evaluation of the Implementation of Furniture Independence Guidance for Prisoners in Manokwari Class IIB Prison. Furniture independence guidance is one form of guidance in Manokwari Class IIB Prison where the results of this guidance production can be used as income for Manokwari Class IIB Prison itself. However, in the implementation process, this furniture independence guidance program did not run well due to obstacles, so innovation is needed to make the implementation of this program run well in Manokwari Class IIB Prison.